Klasterisasi Penjualan Pakaian untuk Meningkatkan Strategi Penjualan dengan Menggunakan K-Means - Chandra Purnama; Wina Witanti; Puspita Nurul Sabrina (Journal of Information Technology, 2022)
The growing competition in the industrial world, especially to meet the primary needs of humans who are always evolving and changing, it requires a way and also a solution that can find a pattern in increasing sales and marketing of goods in the company, one of which is the use of sales data. Inaccurate sales strategy, causing high cost overruns and uneconomical, this is very dangerous for business people. One technique that can be used to assist in improving an effective sales strategy is by utilizing available sales data. As a form of efficiency in its use, it is deemed necessary to add a system that is used to predict an object. Clustering is a process to group data into several clusters or groups so that the data in one cluster has the maximum level of similarity and the data between clusters has the minimum similarity. Sales data are grouped based on the similarity of the data so that data with the same characteristics are in one cluster and one of the attributes used is the type of clothing and sales.